A terceirização da advocacia pública no poder executivo dos municípios tocantinenses sob a ótica da economicidade - Araújo, Dênis Luciano Pereira (Universidade Federal do Tocantins, 2023)
The present research aimed to elucidate whether the outsourcing of legal services by the municipal entities of Tocantins, in view of their low financial capacity and the lack of obligation to create public offices, is a more economical solution for the Municipal Executive Branch than the execution by public servants. The research, of a descriptive nature, adopted a qualitative and quantitative approach, analyzed and systematized the expenses with the outsourcing of legal services performed by the agencies that made the Executive Branch of the municipalities of Tocantins, from the point of view of economy, for the fiscal year 2021. The methodology used was based on mathematical projections involving the salaries practiced in the Public Administration in comparison with the amounts paid to the outsourced personnel. The result of the research demonstrated that the outsourcing of legal activities was the rule in the institutions that make up the Executive Branch of Tocantins and that, from the standpoint of the Principle of Economicity, they were not economical, since there was an increase in costs, if compared to the salaries paid to public servants.